Konsep penalaran bayani, irfani dan burhani pada pembelajaran aqidah ahlak dalam pendidikan islam - Yayuk Purwati; Aulia Diana Devi (Latifah Pres, 2020)
This paper aims to describe the concept of reasoning bayani, irfani and burhani on the learning of Aqidah Akhlak in Islamic education. aqidah akhlak learning innovations in Islamic education in schools to overcome the growth of children. The direction and purpose of Islamic education is to foster students with early integrity and national loyalty, so that it is necessary to multiply its efforts in the field of science. Some aspects of science that need attention include: First, updating the epistemological method of the history of Islamic civilization and learning from the relevant curriculum organization. Second, the epistemological paradigm reform of Bayani's reasoning aims to be Abid al-Jabiri's trilogy of reasoning, namely Bayani reasoning, Irfani reasoning and Burhani reasoning in the learning of Aqidah Akhlak. All three are very linear reasoning that goes hand in hand but still only bayani is made a top priority. And the third circular linking between the three and all reasoning can complement each other. And thirdly in accordance with the value of global issues in the learning materials aqidah Akhlak, as well as the progress of the times and the complexity of the issues faced by mankind, especially the Muslim community, the issue must be acted on locally but globally. This is a response to the progress of modern architecture, so Islamic religious education in the school is very necessary and needs to be considered its existence.